2019
DOI: 10.3390/su12010191
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Patterns and Driving Forces of Urban Expansion in Coastal Areas: A Study on Urban Agglomeration in the Pearl River Delta, China

Abstract: Since the beginning of the 21st century, the spatial pattern of urban expansion and the mechanism of urbanization in coastal areas have undergone significant changes. This study aims to reveal the spatiotemporal patterns of urban land expansion and analyze the dynamic driving forces of urban agglomeration in the Pearl River Delta of China from 2000 to 2015. The urban-land-expansion intensity index, expansion difference index, and fractal dimension were used to study how the urban land in this area was develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Having examined the Beijing-Tianjin-Hebei urban agglomeration, this study found that the expansion rate of Beijing during 1995-2000 was 2% [67], whereas the expansion rates of eight cities in the YRDR had been higher: CU (2.6%), JH (4.9%), LS (3.1%), MAS (3.7%), NJ (2.8%), WZ (3.8%), and WH (2.2%). The highest expansion rate in the Pearl River Delta urban group was GZ (14.1%) during 2000-2005 [19]. The expansion rate of SZ was 2.6% during 2005-2010 [19].…”
Section: Expansion Rates and Differencesmentioning
confidence: 94%
See 1 more Smart Citation
“…Having examined the Beijing-Tianjin-Hebei urban agglomeration, this study found that the expansion rate of Beijing during 1995-2000 was 2% [67], whereas the expansion rates of eight cities in the YRDR had been higher: CU (2.6%), JH (4.9%), LS (3.1%), MAS (3.7%), NJ (2.8%), WZ (3.8%), and WH (2.2%). The highest expansion rate in the Pearl River Delta urban group was GZ (14.1%) during 2000-2005 [19]. The expansion rate of SZ was 2.6% during 2005-2010 [19].…”
Section: Expansion Rates and Differencesmentioning
confidence: 94%
“…Research on urban spatial clusters began as early as the 1920s, using megalopolis [18], urban agglomeration [19,20], city group, and city cluster to describe such urban spatial organization [21]. Urban agglomerations were initially defined as a central city and several surrounding towns [22].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the Pearl River Delta is a region which gained much attention. As a rapidly urbanizing area, the Pearl River Delta faces a contradiction between urbanization and the eco-environment, which is manifested by the decline in the quantity and quality of natural resources, the increase in urban environmental pollution, and the deterioration of the natural eco-environment, which has severely restricted the sustainable development of the region [15][16][17][18].Thus, some studies have addressed the spatial differentiation characteristics of the coordination between urbanization and the eco-environment in the Pearl River Delta [8,13]. However, coordination is generally calculated based on the status quo data, and not on incremental data.…”
Section: Introductionmentioning
confidence: 99%
“…The comprehensive index was used to classify the types of urban expansion in prefecture-level cities, and the spatial distribution difference of urban expansion types in each city was analyzed. (3) Although many scholars have used linear regression [41], ridge regression [42], a geographic detector [43], a spatial econometric model [44], and other methods to quantitatively study the influence of multiple factors on urban land, the existing research pays little attention to the temporal coevolution of urban land area with urban population and GDP. Using the power scaling law, Fei and Zhao [45] calculated the scaling coefficient of urban population and urban land area, as well as that of urban GDP and urban land area.…”
Section: Literature Reviewmentioning
confidence: 99%